Direct and indirect effects of work‒family enrichment: role of gender role ideology. Issue 5 (4th September 2019) - Bansal, Nidhi; Agarwal, Upasna A.
Abstract : Purpose: The purpose of this paper is to examine the antecedents (i.e. work‒family culture and decision latitude) and outcome (innovative workplace behavior (IWB)) of work‒family enrichment (WFE). The study also examines the moderated mediation hypothesis between WFE and outcome, considering work‒life balance (WLB) as a mediator and gender role ideology (GRI) as the moderator. Design/methodology/approach: Data for the study were collected through a questionnaire survey from 426 Indian dual working parents, working in various sectors, through purposive sampling technique. Findings: The study found that work‒family culture and decision latitude are positively related to WFE, which, in turn, results in increased IWB, with WLB acting as its mediator. Further, the study also found a moderating effect of GRI between WFE and WLB relationship; more specifically, the relationship between WFE and balance is stronger for egalitarian employees (high GRI). Research limitations/implications: Using self-reported questionnaire data and a cross-sectional research design is the limitation of this study. Originality/value: The study examines a relatively less focused phenomenon of work‒life interface, that is WFE in one of the underrepresented contexts like India; further, the study extends the range of antecedents and outcomes of WFE. Additionally, it contributes to understand the enrichment‒balance relationship, whereby it explains the role of GRI in developing a balanced perception.